Improving Fine Motor Skills Through Handicraft Activities in Kindergarten Group B - Salbiah Agustini; Muhammad Yusuf; Uswatun Nisa; Herman Taufik (EDUJAVARE: International Journal of Educational Research, 2025)
This classroom action research aimed to improve fine motor skills in children aged 5–6 years old in Group B TK ABA Rahmaniah Banjarbaru through a series of structured handicraft activities. The research was motivated by the observation that most children exhibited underdeveloped fine motor skills, which are essential for daily functioning and school readiness. The intervention consisted of two cycles, each with three sessions, where children created pencil holders from recycled plastic bottles, engaging in cutting, gluing, coloring, and decorating. Data were collected through observation checklists, documentation, and descriptive analysis. The results revealed a significant improvement: children in the "Very Well Developed" category increased from 0% at baseline to 85.7% after the second cycle. The findings confirm that creative handicraft activities provide an effective, enjoyable, and sustainable approach to developing fine motor skills in early childhood. Recommendations are offered for teachers, schools, parents, and future researchers.